2014
DOI: 10.1063/1.4899142
|View full text |Cite|
|
Sign up to set email alerts
|

Structural consequences of hydrogen intercalation of epitaxial graphene on SiC(0001)

Abstract: The intercalation of various atomic species, such as hydrogen, to the interface between epitaxial graphene (EG) and its SiC substrate is known to significantly influence the electronic properties of the graphene overlayers. Here, we use high-resolution X-ray reflectivity to investigate the structural consequences of the hydrogen intercalation process used in the formation of quasi-free-standing (QFS) EG/SiC(0001). We confirm that the interfacial layer is converted to a layer structurally indistinguishable from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…However, the ZL plays an important role in passivating the dangling bonds of the SiC(0001) substrate, so that the overlying graphene layer exhibits truly delocalized π orbitals. An elegant way to remove the undesirable influence of the ZL on the overlying graphene is to prepare so-called quasi-free-standing epitaxial graphene (EG) through decoupling the ZL from the substrate [2] by the intercalation of various elements such as H [5,[10][11][12][13][14][15][16][17], Li [18], Na [19], O [20][21][22], F [2,23], Au [9,24], Cu [25], Fe [26,27], Yb [28], Al [29], Pt [30], Ge [7,31,32] and Si [33][34][35]. Among them, semiconducting elements in group IV, like Si and Ge, turn out to be easily intercalated by deposition at room temperature (RT) and…”
Section: Introductionmentioning
confidence: 99%
“…However, the ZL plays an important role in passivating the dangling bonds of the SiC(0001) substrate, so that the overlying graphene layer exhibits truly delocalized π orbitals. An elegant way to remove the undesirable influence of the ZL on the overlying graphene is to prepare so-called quasi-free-standing epitaxial graphene (EG) through decoupling the ZL from the substrate [2] by the intercalation of various elements such as H [5,[10][11][12][13][14][15][16][17], Li [18], Na [19], O [20][21][22], F [2,23], Au [9,24], Cu [25], Fe [26,27], Yb [28], Al [29], Pt [30], Ge [7,31,32] and Si [33][34][35]. Among them, semiconducting elements in group IV, like Si and Ge, turn out to be easily intercalated by deposition at room temperature (RT) and…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Thermally generated atomic hydrogen (H) is also one of the few known etchants for SiC (Refs. [41][42][43][44][45] Therefore, we have conducted a combined temperature programmed desorption (TPD) and x-ray photoelectron spectroscopy (XPS) investigation of the thermal desorption of molecular hydrogen (H 2 ) and various C, O, and F related surface species from ex-situ aqueous hydrogen fluoride (HF) and in-situ remote H-plasma cleaned 6H-SiC (0001) surfaces. 39 and 40) as well as producing quasifree standing graphene on SiC (0001) surfaces via hydrogen intercaltion.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that by intercalating hydrogen between the SiC and the buffer layer, the buffer layer transforms reversibly to a normal graphene layer ( Figure 8c). This newly formed graphene layer is simply vertically displaced by 2.1Å along with the other graphene layers on top, if there are any, as shown by high-resolution X-ray reflectivity [102]. Moreover, when the hydrogen is intercalated in a monolayer graphene film, the monolayer graphene electronic structure transforms into that of an AB-stacked bilayer ( Figure 8d).…”
Section: Buffer Layermentioning
confidence: 99%